Carbonate sedimentation and effects of eutrophication observed at the Kališta subaquatic springs in Lake Ohrid (Macedonia) - M. Matter; F. S. Anselmetti; B. Jordanoska; B. Wagner; M. Wessels; A. Wüest (Biogeosciences, 2010)
To date, little is known about the role of spring waters with respect to authigenic carbonate precipitation in a shallow lacustrine setting. Lake Ohrid, located in Southeastern Europe, is a large lake fed to over 50% by karstic springs of which half enter subaquatically and influence significantly its ecology and species distribution. In order to evaluate how sedimentological processes are influenced by such shallow-water springs, the Kališta subaquatic spring area in the north west of Lake Ohrid was investigated by a sidescan sonar survey and with sediment traps and three transects of gravity short cores. Results indicate that sedimentation in the spring area is dominated by authigenic carbonate precipitation. High sedimentation rates and evidences for bio-induced precipitation processes were observed in the water column and in the sediments. Two distinct stratigraphic units characterize the shallow subsurface, both composed of carbonate silts with high carbonate contents of up to 96%, but differing in color, carbonate content and diatom content. A chronological correlation of the cores by radiocarbon dates and 137Cs activities places the transition between the two stratigraphic units after ~1955 AD. At that time, coastal sedimentation changed drastically to significantly darker sediments with higher contents of organic matter and more abundant diatoms. This change coincides with the recent human impact of littoral eutrophication.